2006
DOI: 10.1002/pros.20504
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids modulate α1‐adrenoceptor‐stimulated Ca2+ elevation in human cultured prostatic stromal cells

Abstract: These results indicate that sex steroids modulate the activities of HCPSCs through the regulation of both receptors and signal transduction processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In cultured neurons, we have found that flutamide antagonizes classic genomic actions of T and DHT but mimics rather than blocks the nongenomic neuroprotective actions of these androgens [230]. Of particular interest are novel compounds that bind AR but have altered interactions with AR binding pocket side chains that underlie tissue specificity.…”
Section: Emerging Strategies Of Hormone-related Therapies In Alzhmentioning
confidence: 99%
“…In cultured neurons, we have found that flutamide antagonizes classic genomic actions of T and DHT but mimics rather than blocks the nongenomic neuroprotective actions of these androgens [230]. Of particular interest are novel compounds that bind AR but have altered interactions with AR binding pocket side chains that underlie tissue specificity.…”
Section: Emerging Strategies Of Hormone-related Therapies In Alzhmentioning
confidence: 99%
“…More recent cell culture experiments have also shown that sex hormones have varied effects on prostate smooth muscle cell contractility. Slight changes in the ratio of androgen to oestrogen have been shown to result in dramatic changes in calcium influx in prostatic stromal cells (Nguyen et al 2007). Rather than changing ratios, an earlier study used single concentrations of oestradiol and testosterone and found that cell lines from different patients responded differently to hormone treatment, with some lines showing increased myosin expression after testosterone and oestradiol treatment and others showing no change (Smith et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that the expression of smooth muscle cell markers is influenced by oestradiol treatment, however, the same treatment had little impact on the growth of smooth muscle cell cultures (Zhang et al 1997). A recent study, also using cell culture techniques, showed that at certain concentrations, testosterone, oestradiol and dihydrotestosterone, either alone or in combination, influenced the agonist-induced activity of human cultured prostatic stromal cells through regulation of a-and b-adrenoceptors and/or signal transduction pathways (Nguyen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this finding indicates that activation of prostate α1‐adrenoceptors is coupled to the signaling of ERK1/2 in the human prostate . α 1 ‐Adrenoceptor antagonists are used to treat BPH, as pharmacological α 1 ‐adrenocepto blockade, thought to relax prostatic and bladder neck smooth muscle tone, has been shown to increase urinary flow rate and improve symptoms in BPH patients …”
Section: Introductionmentioning
confidence: 97%